Gambaran Mekanisme Koping Keluarga dengan Anggota Terinfeksi COVID-19 di Kelurahan Cipinang Muara" - Slametiningsih Slametiningsih; Salma Nadila Hernanda (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT During the COVID-19 pandemic, family members were not allowed to stay with patients hospitalized due to the virus. This restriction can impact the psychological condition of the family, including the coping strategies they use. Coping strategies include Problem Focused Coping, Emotion Focused Coping, and Dysfunctional Coping. This study aims to describe the coping mechanisms of families with members hospitalized due to COVID-19. Research Method This study used a descriptive method with total sampling technique. The sample consisted of 53 respondents. The measurement tool used was the Brief COPE Questionnaire. The research was conducted from June 3 to July 3, 2021. Research Results The results showed that 55% of families with COVID-19 patients hospitalized used Problem Focused Coping strategies. This strategy involves active efforts to manage or change the situation causing stress. Conclusion Families of COVID-19 patients in Cipinang Muara used adaptive coping strategies, especially Problem Focused Coping, while caring for their sick family members. Suggestions Local health services are recommended to continue providing counseling and psychoeducation services to families of COVID-19 patients to support their mental health. Additional Conclusion The coping strategy used by families with members infected with COVID-19 in Cipinang Muara is Problem Focused Coping, which includes efforts to seek information, planning, and careful organization to manage the stressful situation. Keywords: COVID-19, Family Coping, Family Members  ABSTRAK Selama pandemi COVID-19, anggota keluarga tidak diperbolehkan menunggu pasien yang dirawat di rumah sakit. Hal ini dapat mempengaruhi kondisi psikologis keluarga, termasuk dalam hal strategi koping yang mereka gunakan. Strategi koping meliputi Problem Focused Coping, Emotion Focused Coping, dan Dysfunctional Coping. Penelitian ini bertujuan untuk menggambarkan mekanisme koping keluarga yang memiliki anggota dirawat di rumah sakit. Metode Penelitian Penelitian ini menggunakan metode deskriptif dengan teknik sampling total. Jumlah sampel yang diteliti adalah 53 responden. Alat ukur yang digunakan adalah Brief COPE Questionnaire. Penelitian dilaksanakan dari 3 Juni hingga 3 Juli 2021. Hasil Penelitian Hasil penelitian menunjukkan bahwa 55% keluarga pasien COVID-19 yang dirawat di rumah sakit menggunakan strategi Problem Focused Coping. Strategi ini melibatkan usaha aktif untuk mengatasi atau mengubah situasi yang menyebabkan stres. Kesimpulan Keluarga pasien COVID-19 di Kelurahan Cipinang Muara menggunakan strategi koping yang adaptif, terutama Problem Focused Coping, selama merawat anggota keluarga yang sakit. Saran Pelayanan kesehatan setempat disarankan untuk terus memberikan layanan konseling dan psikoedukasi kepada keluarga pasien COVID-19 untuk mendukung kesehatan mental mereka. Kesimpulan Tambahan Strategi koping yang digunakan oleh keluarga dengan anggota yang terinfeksi COVID-19 di Kelurahan Cipinang Muara adalah Problem Focused Coping, yang mencakup usaha untuk mencari informasi, perencanaan, dan pengaturan yang matang untuk mengatasi situasi stres. Kata Kunci: COVID 19, Koping Keluarga, Anggota Keluarga